Analisis Pelaksanaan Penilaian Akhir Tahun Di Sekolah Dasar Negeri kecamatan Indralaya Utara Kabupaten Ogan Ilir - Yuswardi, Yuswardi; Nawawi, Effendi; Hestirinaih, Deby Chintia (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
The End-of-Year Assessment is an activity carried out by educators to measure students' competency achievements at the end of the even semester. The implementation of the End-of-Year Assessment at the North District Elementary School in Ogan Ilir Regency already uses an online system or information technology-based approach with a Local Area Network (LAN) network. Some of the challenges faced in the implementation of the End-of-Year Assessment at the North District Elementary School include a lack of facilities, unstable internet connectivity, no specific time limit for the assessment, insufficient teacher competence in handling the assessment, with 40 percent of teachers not fully understanding the 2013 Curriculum. Some teachers still face difficulties in conducting the end-of-year assessment at the elementary school level. The objective of this research is to understand, describe, and analyze the implementation of the End-of-Year Assessment at the North District Elementary School in Ogan Ilir Regency. This research employs a descriptive approach with a qualitative method. The Management Implementation Theory according to Henry Fayol (2004:37) is used in this research, which consists of Planning, Organizing, Directing, Coordinating, and Supervising. The results show that some aspects are running well, while others are facing challenges, such as the End-of-Year Assessment implementation at the North District Elementary School in Ogan Ilir Regency. The planning involves holding meetings for the formation of the assessment committee based on the official decree, but there are challenges related to inadequate facilities like computers, limited internet connectivity, and insufficient teacher competence in conducting the End-of-Year Assessment.